1999
DOI: 10.1177/106342669900700204
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Exposure, Protective Factors, and Mental Health Functioning of Substance-Abusing and Dependent Juvenile Offenders

Abstract: This study examined the linkages of trauma exposure and protective factors with important aspects of mental health and behavioral functioning in a sample of youth presenting serious clinical difficulties. In general, results suggest that the effects of trauma vary considerably with the nature of the trauma. Specifically, findings indicated that, after controlling for important third variable explanations, violence exposure was linked with adolescent criminal offending, whereas sexual abuse was linked with psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…Prior research suggests a link between childhood family trauma and the development of delinquent behavior (Brown et al, 1999; McCord, 1983), with some research suggesting that higher rates of family dysfunction in delinquent girls increases the risk for trauma exposure and the development of trauma-related mental health problems (Lewis et al, 1991; Smith et al, 2006). Researchers also have suggested a specific link between childhood trauma experiences and the development of later delinquency.…”
Section: The Relationship Between Childhood Trauma Delinquency and Smentioning
confidence: 99%
“…Prior research suggests a link between childhood family trauma and the development of delinquent behavior (Brown et al, 1999; McCord, 1983), with some research suggesting that higher rates of family dysfunction in delinquent girls increases the risk for trauma exposure and the development of trauma-related mental health problems (Lewis et al, 1991; Smith et al, 2006). Researchers also have suggested a specific link between childhood trauma experiences and the development of later delinquency.…”
Section: The Relationship Between Childhood Trauma Delinquency and Smentioning
confidence: 99%
“…The relationship between childhood abuse and adulthood substance misuse is widely documented (Brems & Namyniuk, 2002; Liebschutz et al, 2002; Widom & Hiller-Sturmhofel, 2001). Adult victims of childhood abuse have a proclivity to use drugs and alcohol (Brems, Johnson, & Neal, 2004), experience heightened psychiatric symptomatology (Bulik, Prescott, & Kendler., 2001; Kendler et al, 2000; Knisely, Barker, Ingersoll, & Dawson, 2000); present with diagnosable psychopathology (Brems & Namyniuk, 2002; Brown, Henggeler, Brondino, & Pickrel, 1999; Browne & Finkelhor, 1986; Polusny & Follette, 1995; Scher & Twaite, 1999), engage in increased criminal activity, and present behavior problems that require specialized treatment (Easton, Swan, & Sinha, 2000; Westermeyer, Wahmanholm, & Thuras, 2001). Brems, et al (2004) have recommended identifying caregivers with histories of childhood abuse early as a first step to treatment interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to incarcerated youth, Brown, Henggeler, Brondino, and Pickrel (1999) found that sexually abused youth had higher rates of internalizing problems and those exposed to domestic violence had higher rates of externalizing problems. For psychiatric comorbidity, sexual abuse accounted for 8% of the variance, second only to gender in strength.…”
Section: Maltreatment and Incarcerated Youthmentioning
confidence: 99%